If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -11s = 45 Solving 12 + -11s = 45 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -11s = 45 + -12 Combine like terms: 12 + -12 = 0 0 + -11s = 45 + -12 -11s = 45 + -12 Combine like terms: 45 + -12 = 33 -11s = 33 Divide each side by '-11'. s = -3 Simplifying s = -3
| b*b^2= | | 15=-11c+4 | | x+3y+2-3x-5y=4 | | y^3*y^2= | | 4-k/5=18 | | 0.006x-11440/x^2=0 | | 13/4-x/2 | | 6y=4-2x | | 11/6x-4 | | -19=4+3x | | 7/4+9/4 | | 15=6+m/6 | | -2/3u-8/7=-1/2 | | c+l/c-2=4/7 | | 4x-2=28.4 | | 12d-6=138 | | 2+m/3=0 | | 4+4x/5+3-x/2=41/10 | | 17a^2+9b^2=X | | 5+k/9=-31 | | 5(x-7)=3/2x+15 | | 9/w=-6 | | -84+4k=102 | | 17a+9b=x | | x=-6663/209 | | x+1=5+5x | | 24=-3n+9n | | -28.24x+342.5=-38.69x+9.35 | | -6-5x=39 | | (x-4+5i)(x-4-5i)=0 | | -7a+3a=-12 | | 5t+3t=-16 |